Inverse Design of a Broadband and Compact Silicon Three-Mode Multiplexer for On-Chip Optical Interconnect with a 705 nm Bandwidth - Sun, Aolong; Deng, Xuyu; Xing, Sizhe; Yuan, Yuqin; Tan, Hua; Hu, Fangchen; Huang, Ouhan; Chi, Nan; Zhang, Junwen (Asia Communications and Photonics Conference and Exhibition, 2024)
We inversely design a pixelated ultra-broadband three-mode multiplexer on SOI with a record bandwidth of 705 nm. Numerical results show that loss is less than 2.03 dB over the entire wavelength range from 1458-2163 nm.